2020
DOI: 10.1109/access.2020.3025241
|View full text |Cite
|
Sign up to set email alerts
|

DNA Strands Level Scrambling Based Color Image Encryption Scheme

Abstract: In the past, many image encryption schemes have been developed through the swapping operations at the different levels of granularity. These levels span bits, Deoxyribonucleic acid (DNA) molecules, pixels, blocks of pixels. In this study, a new scheme for the encryption of color images based on the DNA strands level scrambling (DNASLS) and chaotic system has been proposed. After a color image is input, it is decomposed into the red, green and blue components. After it, these components are merged to form a big… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…The MAE is another statistical metric used to evaluate the quality of an image encryption algorithm. It measures the average absolute difference between the pixel values of a plaintext image and its cipher image [56]. A lower MAE value indicates a greater similarity between the plaintext image and its cipher, whereas a higher MAE value indicates a lower similarity between the plaintext image and its cipher; therefore, a higher MAE value means higher-quality encryption.…”
Section: Mean Absolute Errormentioning
confidence: 99%
“…The MAE is another statistical metric used to evaluate the quality of an image encryption algorithm. It measures the average absolute difference between the pixel values of a plaintext image and its cipher image [56]. A lower MAE value indicates a greater similarity between the plaintext image and its cipher, whereas a higher MAE value indicates a lower similarity between the plaintext image and its cipher; therefore, a higher MAE value means higher-quality encryption.…”
Section: Mean Absolute Errormentioning
confidence: 99%
“…Basically, the plain image has a very high correlation with adjacent pixels and has a lot of redundant pixel values. But after the image is encrypted, the correlation between adjacent pixels should decrease significantly [4], [21]. Thus, the redundancy is getting smaller, and the correlation value is close to 0.…”
Section: B Correlation Coefficient (Cc) Analysismentioning
confidence: 99%
“…In 2020 [45], (N. Iqbal et al) suggested a novel strategy for color image encryption based on DNA strands level scrambling (DNASLS) and a chaotic system. The streams were generated via an intertwining logistic map (ILM).…”
Section: Color Image Encryption Based On Dnamentioning
confidence: 99%